NTF2-like domain of Tap plays a critical role in cargo mRNA recognition and export - Katahira, Jun; Dimitrova-Paternoga, Lyudmila Nikolova; Hurt, Ed (Nucleic acids research, 2015)
Abstract. Metazoan Tap-p15 (also called Nxf1-Nxt1) and yeast Mex67-Mtr2 heterodimers are the general mRNA export receptors. The RNA binding activity of Tap-p15